Experimental investigation of the confinement effect on a flame impinging a ceiling in an enclosure. (June 2021) - Wang, A.J.; Manescau, B.; Chetehouna, K.; De Izarra, C.; Rudz, S.
Abstract: This experimental study highlights the confinement effect on a flame impinging a ceiling in confined or semi-confined environment. The enclosure used in this study represents a 1:10 scale model of a student compartment with two possible openings: a door and a window. It is developed based on the conservation of the Froude number in scaling law. The objective of this work is to provide explanations in terms of fire safety on thermal phenomena that can occur during fires in closed environments, for example in a room of a university residence, regarding eight heat rates release of fuel and five confinement levels. A flame oscillation modelling of propane-air flame is proposed and is verified by the experimental results. It is shown both by theoretical modeling and experimental results that the confinement of a compartment has an effect on period time of flame oscillation. Moreover, experimental results show that the confinement level of compartment is a key parameter to characterize vertical temperature evolution both in the center (impinging zone) and near the wall in the enclosure. The correlations for normalized gas temperature rise near the wall are proposed and these temperature evolutions are bounded by the ventilation conditions of the five configurations. Indeed, under condition of equivalence ratio greater than 1, the maximum gas temperature near the wall of a certain heat release rate decreases dramatically with the increasing of configurations' confinement levels, which is associated to the decrease in flame intensity by lack of oxygen with a great criterion of under ventilation.